“SAVE MERATUS”, THE MOTTO OF THE SPIRIT CONSCERVING NATURE AND ANCIENT TRADITION IN HULU SEUNGAI TENGAH REGENCY - Berry Nahdian Forqan; Septi Ariadi; Bagong Suyanto (RADJA PUBLIKA, 2025)
Global environmental issues are in the spotlight of various parties in keeping the earth sustainable. As happened in Hulu Sungai Tengah district, by raising the slogan